Elucidation of the Conformational Transition of Oligopeptidase B by an Integrative Approach Based on the Combination of X-ray, SAXS, and Essential Dynamics Sampling Simulation - Vladimir V. Britikov; Vladimir I. Timofeev; Dmitry E. Petrenko; Elena V. Britikova; Alena Y. Nikolaeva; Anna V. Vlaskina; Konstantin M. Boyko; Anna G. Mikhailova; Tatiana V. Rakitina (Crystals, 2022)
Oligopeptidase B (OPB) is the least studied group from the prolyl oligopeptidase family. OPBs are found in bacteria and parasitic protozoa and represent pathogenesis factors of the corresponding infections. OPBs consist of two domains connected by a hinge region and have the characteristics of conformational dynamics, which include two types of movements: the bridging/separation of α/β-hydrolase catalytic and β-propeller-regulatory domains and the movement of a loop carrying catalytic histidine, which regulates an assembly/disassembly of the catalytic triad. In this work, an elucidation of the interdomain dynamics of OPB from Serratia proteamaculans (SpOPB) with and without modification of the hinge region was performed using a combination of X-ray diffraction analysis and small-angle X-ray scattering, which was complemented with an essential dynamics sampling (EDS) simulation. The first crystal structure of catalytically deficient SpOPB (SpOPBS532A) with an intact hinge sequence is reported. Similarly to SpOPB with modified hinges, SpOPBS532A was crystallized in the presence of spermine and adopted an intermediate conformation in the crystal lattice. Despite the similarity of the crystal structures, a difference in the catalytic triad residue arrangement was detected, which explained the inhibitory effect of the hinge modification. The SpOPBS532A structure reconstituted to the wild-type form was used as a starting point to the classical MD followed by EDS simulation, which allowed us to simulate the domain separation and the transition of the enzyme from the intermediate to open conformation. The obtained open state model was in good agreement with the experimental SAXS data.